Wind turbine power converter fault diagnosis using DC-link voltage time–frequency analysis. Issue 4 (August 2019) - Ismail, Adla; Saidi, Lotfi; Sayadi, Mounir
With the developments in power electronic devices, there is increasing use of the insulated gate bipolar transistor devices in power converters. Power converters are more and more gaining attention in the wind energy conversion system. In this article, a grid-connected wind energy conversion system is considered. Wind energy conversion system optimal operation requires a diagnostic method for back-to-back power converter to be addressed in detail in this article. Therefore, an open-circuit switching fault diagnosis method for a back-to-back power converter is developed to improve the system reliability and optimize the produced power and also achieve its real operational cost. In this work, we investigate only the DC-Link voltage signal and we use the time–frequency analysis to achieve the diagnosis purpose. The scheduled diagnosis approach is divided into two tasks: the first one is the fault detection task and the second one is the fault localization task. The main novelty of the proposed diagnosis approach is to localize the appropriate faulty power converter, that is, rotor side power converter or grid side power converter. Also, this approach is able to localize faults when there is a simultaneous fault on both power converters. Simulations are carried out to verify the robustness of the proposed diagnosis approach. The achieved simulation results would help in diagnosing of Back-to-back power converter that would expectedly cancel the traditional diagnosis method.